COMPUTATIONAL STUDY OF GRAPHITE AS HYDROGEN STORAGE MATERIAL USING DENSITY FUNCTIONAL THEORY METHODS - Gunawan, Rahmat
Interaction studies of graphite component as hydrogen storage materials have been investigated theoretically with density functional theory method or DFT. In this calculation, the material will be compared with the graphite modified namely graphite intercalated compounds or GICs, especially by alkali metal intercalates (Li, Na and K). The properties of the electronic structure, energetics and the charge contribution of atomic orbital in the hydrogen- graphite system, GICs, and hydrogen-GICs are studied through the calculation approach of gradient-corrected PBE (Perdew-Burke-Ernzerhof ) for the acqui- sition of exchange-correlation energy. This calculation is further strengthened by the use of plane wave basis set, and calculation of electron-nucleus interac- tions using Vanderbilt ultrasoft pseudopotential. Computational study yielded four main relaxation of molecular geometry, the determination of the electronic energy band structure, density of energy state, and the contribution of atomic orbital of system through analysis of the charge density differences.